A novel fluorescence assay for resveratrol determination in red wine based on competitive host-guest recognition. (15th June 2019) - Li, Can-Peng; Tan, Shuang; Ye, Hanzhang; Cao, Jun; Zhao, Hui
Highlights: A novel fluorescence assay for resveratrol determination in red wine was presented. The approach was based on fluorescence resonance energy transfer through competitive recognition. The assay exhibited high selectivity towards resveratrol. The method is label-free, simple, and rapid for resveratrol determination. The competitive recognition interaction was determined using a molecular docking study. Abstract: A label-free fluorescence assay for resveratrol determination is presented for the first time. The approach was based on fluorescence resonance energy transfer (FRET), via competitive supramolecular recognition, between p-sulfonated calix[6]arene (CX6)-modified reduced graphene oxide (CX6@RGO) and a probe-resveratrol complex. The probe molecule (Rhodamine B or rhodamine 123) had a strong fluorescence signal, and its fluorescence was quenched by CX6@RGO, based on FRET. When the target molecule was added to CX6@RGO, the probe molecule was displaced by resveratrol, and a host-guest complex, CX6@RGO-resveratrol formed, turning-on the fluorescence signal. Fluorescence intensity of the CX6@RGO-probe complex increased linearly with increased resveratrol concentrations (2.0–40.0 μM). The proposed approach was used to determine resveratrol in red wine with satisfactory detection limits and recoveries. Compared with traditional determination methods, our procedure is advantageous because it saves time, is easy to operate, and does not require sample pretreatment.